Phosphate-bonded refractories in hydrogen containing atmosphere - T. Leber; D. Kenn; F. Matt; M. Scheller; T. Tonnesen; J. Gonzalez-Julian (Open Ceramics, 2024)
In the transition to a CO2-neutral industry, traditional carbon fuel-based systems must be replaced by sustainable fuel systems such as hydrogen. This change implies a different atmosphere during the operation at high temperature, which is a big challenge for refractory lining materials. This study focuses on four different phosphate-bonded refractories, which are generally characterised by fast drying times, adequate refractoriness, and excellent abrasion and slag resistances. Two phosphate-bonded industrial refractory masses, one based on corundum and the other on fireclay, are tested under corrosive conditions. Two model systems are considered to provide a fundamental view of the behaviour. These focus on smaller grain sizes, reduced silica content and proportionally contain higher amounts of different phosphate-based binders. The first model system contains mainly magnesia and is bound by sodium polyphosphate. The other consists of alumina and is bonded with monoaluminium phosphate. All materials are exposed in a dilute, 9Ar 1H2, hydrogen atmosphere at various temperatures and holding times.Corrosion experiments up to 1500 °C have been carried out using a tube furnace with the above conditions. The microstructure, and in particular the binder phase, was characterized by SEM and EDS. Microstructural components undergoing reaction or loss will be identified and their behaviour and movement in the system will be considered. Particular attention is paid to the phosphorus components, their possible reduction and their influence on the binder phase.